1993
DOI: 10.1038/366525a0
|View full text |Cite
|
Sign up to set email alerts
|

Human basophil degranulation is not triggered by very dilute antiserum against human IgE

Abstract: We have attempted to reproduce the findings of Benveniste and co-workers, who reported in 1988 that degranulation of human basophil leukocytes is triggered by very dilute (10(2)-10(120)) antiserum against IgE. The results were contrary to conventional scientific theory and were not satisfactorily explained. Following as closely as possible the methods of the original study, we can find no evidence for any periodic or polynomial change of degranulation as a function of anti-IgE dilution. Our results contain a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0
4

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(52 citation statements)
references
References 1 publication
1
47
0
4
Order By: Relevance
“…36 This led to a fierce debate, and Benveniste's results appear not to be reproducible. 37 However, in 1999 a multi-centre experiment using a related method showed positive results. 38 The leading current hypothesis on the action of ultramolecular dilutions is the 'information medicine' hypothesis: 'water is capable of storing information relating to substances with which it has previously been in contact, and subsequently transmitting this information to pre-sensitised biosystems'.…”
Section: How It May Workmentioning
confidence: 99%
“…36 This led to a fierce debate, and Benveniste's results appear not to be reproducible. 37 However, in 1999 a multi-centre experiment using a related method showed positive results. 38 The leading current hypothesis on the action of ultramolecular dilutions is the 'information medicine' hypothesis: 'water is capable of storing information relating to substances with which it has previously been in contact, and subsequently transmitting this information to pre-sensitised biosystems'.…”
Section: How It May Workmentioning
confidence: 99%
“…However, it should be noted that other studies of equal quality have not been able to reproduce these findings. [28][29][30] Another example is a series of studies that found that the administration of an oral dose of a homeopathic preparation of arsenic trioxide protected mice from the detrimental changes in proteins, enzymes, DNA, and RNA caused by one injection of arsenic trioxide of 1mg/kg bodyweight, corroborating the 1997 findings of Weigant et al [31][32][33][34][35][36][37] Overall, the results from studies assessing the ability of very dilute solutions to have biological effects are mixed. Although, high quality research shows that homeopathic preparations do have measurable effects on biological systems; to date, studies have not successfully settled the original dilemma concerning a mechanism of action for very dilute solutions.…”
Section: Physical Experiments In Dilution Researchmentioning
confidence: 70%
“…3,[6][7][8] Pharmacists should also be aware that the data assessing the efficacy of homeopathy are mixed-there are rigorous, reproducible studies that show homeopathy is effective, 39,[42][43][44] and equally scientifically sound studies that show it is not. [28][29][30][80][81][82] A similar situation exists with respect to in vivo studies of homoeopathic products used to treat plants and animals. 83,84 Pharmacists should also be aware that there is currently no plausible mechanism of action postulated for homeopathy; even homeopathic doctors do not claim to know how it works.…”
Section: What Should Pharmacists Know About Homeopathy?mentioning
confidence: 99%
“…We have noted fifteen discrepancies in methodology , of which three are cardinal errors: (1) the authors did not eliminate blood that was unreactive to ponderal anti-IgE antiserum, and which selfevidently would not react to the same highly diluted antiserum; (2) they did not test the high dilutions and controls (themselves inadequate, proper controls being diluted dummy antibody) on the same blood samples, an experimental sine qua non ; and (3) they added a centrifugation step after incubation, thereby impairing accurate counting of activated basophils 2 ,5. These errors alone are enough to invalidate their whole attempt. The procedures involved in our basophil test are complex; it is a pity the authors did not consult us before embarking on it .…”
Section: Sir -Hirst Et Al 'S C1aimmentioning
confidence: 99%